Middle East Respiratory Syndrome Coronavirus Antibody Reactors Among Camels in Dubai, United Arab Emirates, in 2005. Issue 2 (24th January 2014) - Alexandersen, S.; Kobinger, G. P.; Soule, G.; Wernery, U.
Summary We tested, using a low starting dilution, sequential serum samples from dromedary camels, sheep and horses collected in Dubai from February/April to October of 2005 and from dromedary camels for export/import testing between Canada and USA in 2000–2001. Using a standard Middle East respiratory syndrome coronavirus (MERS‐CoV) neutralization test, serial sera from three sheep and three horses were all negative while sera from 9 of 11 dromedary camels from Dubai were positive for antibodies supported by similar results in a MERS‐CoV recombinant partial spike protein antibody ELISA. The two negative Dubai camels were both dromedary calves and remained negative over the 5 months studied. The six dromedary samples from USA and Canada were negative in both tests. These results support the recent findings that infection with MERS‐CoV or a closely related virus is not a new occurrence in camels in the Middle East. Therefore, interactions of MERS‐CoV at the human–animal interface may have been ongoing for several, perhaps many, years and by inference, a widespread pandemic may be less likely unless significant evolution of the virus allow accelerated infection and spread potential in the human population.